Dual‐Carbon Confined SnP2O7 with Enhanced Pseudocapacitances for Improved Li/Na‐Ion Batteries. Issue 14 (20th July 2021) - Guo, Xinzhu; Wan, Zhengwei; Wei, Di; Zeng, Xiaomin; Li, Zeheng; Jiang, Wei; Wang, Hongxun; Ling, Min; Li, Hui; Liang, Chengdu
Abstract: Tin‐based materials have obtained much attention in lithium‐ion batteries (LIBs) due to high specific capacity. However, the large volume change and poor electroconductivity hinder their further practical application. Herein, a C18 N12 (CN)‐wired amorphous carbon coated pyrophosphate tin (SnP2 O7 @C) ultrafine nanoparticles composite (SnP2 O7 @C/CN) is prepared by solvothermal‐calcination with phytic acid (PA) as phosphorus and carbon sources simultaneously. Ultrafine‐nanocrystallization and dual‐carbon doping enhances the pseudocapacitance of SnP2 O7 @C/CN and thus, exhibit good electrochemical performance and high lithium/sodium storage efficiency. As anode of LIBs, the SnP2 O7 @C/CN exhibits a superior reversible capacity of 557.3 mAh/g after 100 cycles at a current density of 0.2 A/g and a conspicuous cyclability of 352.3 mAh/g after 800 cycles at 1 A/g. For sodium‐ion batteries (SIBs), the stable discharge capacity of SnP2 O7 @C/CN electrode is 91.5 mAh/g after 800 cycles at a high current density of 2 A/g. This strategy can increase active sites, provide large electrolyte/electrode contact area, and improve electroconductivity. Moreover, SnP2 O7 @C/CN electrode provides a buffer space for structural strains caused by volume changes during charging and discharging. Abstract : A C18 N12 (CN)‐wired amorphous carbon coated pyrophosphate tin (SnP2 O7 @C) ultrafine nanoparticles composite (SnP2 O7 @C/CN) is prepared by solvothermal‐calcination with phytic acid (PA) as phosphorus and carbon sources simultaneously. Ultrafine‐nanocrystallization and dual‐carbon doping enhances the pseudocapacitance of the composite leading to excellent electrochemical performance and high lithium/sodium storage efficiency. This strategy can increase active sites, provide large electrolyte/electrode contact area, and improve electroconductivity. Moreover, SnP2 O7 @C/CN electrode provides a buffer space for structural strains caused by charging and discharging volume changes.